2021
DOI: 10.1186/s12920-021-00964-5
|View full text |Cite
|
Sign up to set email alerts
|

Broadening our understanding of genetic risk for scleroderma/systemic sclerosis by querying the chromatin architecture surrounding the risk haplotypes

Abstract: Background Genetic variants in the human leukocyte antigen (HLA) locus contribute to the risk for developing scleroderma/systemic sclerosis (SSc). However, there are other replicated loci that also contribute to genetic risk for SSc, and it is unknown whether genetic risk in these non-HLA loci acts primarily on the vasculature, immune system, fibroblasts, or other relevant cell types. We used the Cistrome database to investigate the epigenetic landscapes surrounding 11 replicated SSc associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…We used the BedTools software to assess for enrichment in CD14+ human monocytes, following the method described by Poppenberg et al. ( 22 ). Briefly, we mined publicly available CD14+ H3K4me1 and H3K27ac ChIPseq using the Cistrome database…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the BedTools software to assess for enrichment in CD14+ human monocytes, following the method described by Poppenberg et al. ( 22 ). Briefly, we mined publicly available CD14+ H3K4me1 and H3K27ac ChIPseq using the Cistrome database…”
Section: Methodsmentioning
confidence: 99%
“…We therefore adapted the method described by Poppenberg et al. ( 22 ) to identify TAD structures that encompass the JIA risk haplotypes in monocytes. In brief, we first analyzed a publicly available HiC data set ( 26 ) using Juicebox software ( 27 ) following the method described by Kessler et al.…”
Section: Methodsmentioning
confidence: 99%
“…Enrichment analysis: H3K4me1/H3K27ac ChIPseq data -We investigated the presence of potential enhancers within the JIA risk regions by defining enrichment (compared to genome background) for H3K4me1 and H3K27ac histone marks from publicly available ChIPseq data. We used the BedTools software to assess for enrichment in CD14+ human monocytes, following the method described by Poppenberg et al (22) Briefly, we mined publicly available CD14+ H3K4me1 and H3K27ac ChIPseq using the Cistrome database (http://cistrome.org/db/#/ ). We first queried a single data set for each H3K4me1 (GEO accession #GSM1003535) and H3K27ac (GEO accession #GSM2818004).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Gasperini et al (25) showed that, on a genome-wide CRISPRi screen, 71% of enhancers regulate genes within the same TAD. We therefore adapted the method described by Poppenberg et al (22) to identify TAD structures that encompass the JIA risk haplotypes in monocytes. In brief, we first analyzed a publicly available HiC data set (26) using Juicebox software (27) following the method described by Kessler et al (8) to identify interacting regions in the monocyte THP-1 cell line.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, many of the different genes assigned to SSc GWAS loci are related to T cell activation and macrophages regulation pathways (11,12), and are shared among immune-mediated diseases, which may be of interest in the drug repositioning of rare diseases like SSc, where there are no specific available treatments (13). However, the majority of single nucleotide polymorphisms (SNPs) associated with SSc map to non-coding regions of the genome that are enriched in enhancer elements, which are often cell-type specific (14,15). These regulatory elements can interact with genes often located hundreds of kilobases away, bypassing in many cases nearby genes (16).…”
Section: Introductionmentioning
confidence: 99%